A high performance UWB MIMO antenna with defected ground structure and U‐shape branches. Issue 2 (25th May 2020) - Tang, Xiaocong; Yao, Zhao; Li, Yang; Zong, Weihua; Liu, Guoxia; Shan, Fukai
Abstract: A binary ultra‐wideband multiple‐input‐multiple‐output (MIMO) antenna is proposed and fabricated. In order to increase the impedance bandwidth and resonance frequency, U‐shaped branches, defected ground structure, folded stepped impedance stubs, and window‐shaped radiation patch slots are analyzed. The total size of the MIMO antenna is 80 mm × 35 mm, and the measured relative impedance bandwidth realizes 131% (2.57‐12.2 GHz). Without the addition of a decoupling structure and a metal isolation bar, the isolation measured by this work is less than −15 dB. The measured antenna gain is between 3.064 and 4.669 dBi. The measured envelope correlation coefficient value is less than 0.005, and diversity gain is almost equal to 10 dB. The channel capacity loss obtained in the measurement is less than 0.4 bit/s/Hz in the bandwidth except for 9 to 10 GHz. Excellent properties make it suitable for modern wireless communication applications.